Demagnetization Analysis and Optimization of Bonded Nd-Fe-B Magnet Rings in Brushless DC Motors - Yinan Wang; Hao Zhan; Yanyan Gong; Mingxu Wang; Juntao Yu; Ze Zhang; Yuanfei Yang; Li Wang (Machines)
Bonded Nd-Fe-B magnets have greater freedom of shape than sintered Nd-Fe-B magnets. The ring structure is one of the typical structures of bonded Nd-Fe-B materials. In this paper, we analyzed the generation and spread of demagnetization fault (DMF) and changes in motor performance. Meanwhile, a BLDC fitted with a bonded Nd-Fe-B magnet ring was analyzed for DMF under actual overload conditions. DMF occurred with obvious localization and variability, which was mainly concentrated on the side of each pole opposite to the direction of the motor’s operation, near the weak magnetic zones. The experimental results show that back electromotive force (EMF) and its harmonic had the same variation trends as the surface radial flux density of the magnet ring. The analysis with the EMF waveform and total harmonic distortion (THD) were proposed as a method for diagnosing the DMF. Finally, this paper presents a modified magnet ring. The anti-demagnetization capability of the modified magnet ring is effectively improved. This research can provide a reference for the design analysis of BLDCs using bonded Nd-Fe-B magnet rings.